Severe Preeclampsia versus HELLP Syndrome: Maternal and Perinatal Outcomes at <34 and ≥34 Weeks’ Gestation - Kınay, Tuğba (Balkan Med J, 2015)
BACKGROUND: Preeclampsia and Hemolysis, Elevated Liver enzymes, Low Platelet (HELLP) syndrome are important disorders affecting the health of both the mother and fetus. Prediction of the maternal and perinatal outcomes at early and late gestational age is important for the management of both disorders. AIMS: The purpose of the study was to investigate adverse maternal and perinatal outcomes in severe preeclampsia and HELLP syndrome cases according to gestational age. STUDY DESIGN: Retrospective cross-sectional study. METHODS: One hundred and ninety-seven pregnancies with severe preeclampsia and 56 pregnancies with HELLP syndrome were included the study. Clinical characteristics and adverse maternal and perinatal outcomes were noted from medical records. Participants were divided into two groups at <34 and ≥34 weeks’ gestation: the severe preeclampsia group and the HELLP syndrome group. The differences between the outcomes in the groups were investigated. Statistical analysis was performed using the Student t test, Fisher Exact test and Yates’ Chi-square test. RESULTS: Eclampsia was more common in HELLP syndrome cases at <34 weeks’ gestation (p 0.028). However, eclampsia rates were statistically similar between groups at ≥34 weeks’ gestation. The requirement for blood products transfusion was higher in the HELLP group at all gestational weeks. No statistical difference was found in perinatal outcomes between severe preeclampsia and HELLP groups at less than and more than 34 weeks’ gestation. CONCLUSION: Eclampsia risk increases in HELLP syndrome, especially at gestations less than 34 weeks. Perinatal morbidity at less than 34 weeks’ gestation and mortality were similar in severe preeclampsia and HELLP syndrome cases at the same gestational age.